“Common good of marriage and the family”: canonical reflections = « Le bien commun du mariage et de la famille » : Réflexions juridico-canoniques = “Il bene comune del matrimonio e della famiglia” : Riflessioni giuridico-canoniche - Pastwa, Andrzej (Philosophy & canon law, 2015)
The initial thesis of the study is John Paul II’s proclamation in the Letter to Family (1994), which states that an individual can exist “for himself” through the sincere gift of self—and, at the same time, fulfill himself as “common good”: “the common good of the whole of the society” and “the common good of marriage and the family” (nn. 10, 11). These latter words give an impulse to undertake an attempt of transforming the profound theological thought of the papal document into conclusions on the canon law plane. The most fundamental ones seem to be: (1) a considerable meaning for the Church matrimonial discipline has its foundation on a realistic vision of a human being; (2) a basis of the contemporary theological and legal doctrine de matrimonio et familia is the structural (ethical) principle of love; (3) the acceptance of the appropriate premises of the juridical anthropology of marriage gives life to all attempts of setting the personalistic dimension of marriage against its legal value; (4) the indissoluble character of marriage is the basis of the common good of the family.